Hydroclimate variability of northern Chilean Patagonia during the last 20 kyr inferred from the bulk organic geochemistry of Lago Castor sediments (45°S). (15th January 2019) - Fiers, Géraldine; Bertrand, Sebastien; Van Daele, Maarten; Granon, Emma; Reid, Brian; Vandoorne, Willem; De Batist, Marc
Abstract: Lago Castor (45°S) contains a continuous sediment record of Patagonian climate and environmental change during the last 20 kyr. Here, we use the bulk elemental and isotopic composition of the organic matter preserved in Lago Castor sediments to reconstruct changes in the supply of organic carbon of terrestrial and aquatic origin to the lake through time. Results show that the lake sedimentary organic matter is composed of variable proportions of lake plankton, terrestrial vegetation, and aquatic macrophytes. Before 17.8 cal kyr BP, aquatic macrophytes were abundant, likely due to the low but rising postglacial lake level. After 17.8 cal kyr BP, accumulation rates of organic carbon of aquatic macrophyte origin became negligible, whereas those of terrestrial origin increased, reflecting weak westerlies and terrestrial vegetation development under a milder climate, respectively. From 9.3 cal kyr BP onwards, accumulation rates of organic carbon from both aquatic macrophytes and terrestrial vegetation increased and peaked between 7.5 and 2.0 cal kyr BP. The latter is interpreted as a period of increased wind strength and precipitation, and is in excellent agreement with the grain-size results previously obtained on the same sediment core. All proxies show a secondary increase in wind strength and precipitation during the last millennium, in agreement with regional high-resolution records of the last 2000 years. These results, which are broadly compatible with regional pollen records during the Holocene, suggest that, at 45°S, the westerlies reached their maximum intensity between 7.5 and 2.0 cal kyr BP and increased again during the last millennium. Graphical abstract: Highlights: OC in Lago Castor originates from terrestrial vegetation, aquatic macrophytes and lake plankton. The proportions of each component were estimated using a 3 end-member mixing model. Accumulation rates of OC from aquatic macrophytes reflect westerly wind strength. At 45°S, the westerlies peaked in 7.5–2.0 cal kyr BP and during the last millennium. New proxy records independent of terrestrial vegetation are needed in Patagonia.